Numerical simulation of a damaged ship cabin flooding in transversal waves with Smoothed Particle Hydrodynamics method. (1st October 2018) - Ming, F.R.; Zhang, A.M.; Cheng, H.; Sun, P.N.
Abstract: Compared to the case in still water, a damaged ship flooding in waves can be more complex with more violent shaking and accompanied by wave breaking and splashing. Therefore, in this work, a numerical study regarding the damaged ship cabin flooding in transversal regular waves is carried out based on a weakly compressible Smoothed Particle Hydrodynamics (WCSPH) method. Firstly, the governing equation, the fluid-structure interface treatment, the non-reflection sponge layer boundary and the information extraction of particle flow field are discussed respectively. Then, the numerical method is validated from two aspects: the experiment of a damaged ship cabin flooding is carried out to test the accuracy of the fluid-structure interaction model and a standard example is employed to validate the regular wave model. Furthermore, the influences of transversal regular waves on the flooding of a damaged ship cabin are explored. The openings at the broadside away from and towards the incident wave are considered. The six-degree-of-freedom (6-DOF) responses of the ship body to the incident waves are focused. This study can provide references for the hydrodynamic performance of damaged ships and decision makings of the rescue after marine accident. Highlights: Dynamic flooding of a damaged ship model is studied with a three-dimensional WCSPH method validated by model experiment. Six-degree-of-freedom motions of a damaged ship model responding to transverse waves are analyzed. The effects of incident wave directions relative to the opening position on the damaged ship responses are investigated.